Gunnar Landtman in Papua 1910 to 1912 - Lawrence, David (ANU Press, 2010)
Despite poverty and neglect the coastal Kiwai of the northern Torres Strait and Fly estuary are a strong and vibrant people with a long tradition of work in the marine industries of the Torres Strait. Regrettably their current social, economic and political problems are marginal to both Papua New Guinea and Australia. Gunnar Landtman's research, undertaken between 1910 and 1912, is still a foundation stone for understanding the position of the Kiwai today. In those two years in Papua, Landtman managed to record a large collection of valuable legends and stories, many of which are still told today. He travelled widely throughout the Torres Strait, the southwest coast of Papua and the Fly estuary and even to the Gulf District. He made a comprehensive collection of Kiwai material culture now housed in the Museum of Cultures in Helsinki and a second, duplicate set for the Cambridge Museum. He also collected some of the earliest examples of Gogodala material culture available for research. In 1913, he published, Nya Guinea färden [New Guinea expedition], a detailed travelogue of his work and life among the Kiwai and, while he wrote a substantial corpus of work on the Kiwai in English, Swedish and Finnish over the next twenty years, this personal account in Swedish has not been translated into English before. It forms a crucial link between Landtman's serious academic works and his intimate personal journey of discovery. The aim of this book is to bring the personal face of the serious anthropologist to greater attention. David Lawrence began studying the Gunnar Landtman collections held by the National Museum of Finland when he was researching customary exchange across the Torres Strait for his doctorate at James Cook University. He was also fortunate to be able to spend two years of fieldwork in the Fly estuary region and visited nearly all the communities described by Landtman. He is a Visiting Fellow at the Resource Management in Asia/Pacific program of The Australian National University and has published works on Kakadu National Park and the Great Barrier Reef Marine Park.